Pengaruh Permainan Olahraga Tradisional Terhadap Peningkatan Kebugaran Jasmani Pada Siswa Kelas V Sekolah Dasar Negeri Dendeng Kabupaten Kupang - Adelaida Missa; Timoteus Ajito; Oded Liunokas; Yoppi Huwae (Journal on Education, 2024)
The problem in this research is the low level of physical fitness among students at SD Negeri Dendeng, Kupang Regency. The aim of this research is to improve the fitness of fifth grade male students at SD Negeri Dendeng through the traditional foreign game Gala and the traditional game Siki doka. The data collection technique uses the TKJI test for the 12-14 year age group. The sample in this study was male students in class V of SD Negeri Dendeng with a total of 28 students. This research uses the Randomized pretest-posttest Control Group Design experimental method. The results of hypothesis testing show that the percentage of training running speed before training in Group 1 of the traditional game Gala Sing (PTGA) was 16.140 seconds (p>0.05) and after training with a running speed of 12.930 seconds (p<0.05) was greater than in Group 1. 2 traditional games Siki doka (PTSD) with running speed before training 16.055 seconds (p>0.05) and after training 14.666 seconds (p<0.05), and the difference in improvement in group 1 traditional game foreign gala = 3.210 seconds greater from group 2 of the traditional game siki doka = 1.389 seconds. With an average increase in physical fitness after training in Group 1 the traditional foreign game Gala had a better effect with an increase percentage of 19.88% greater than in group 2 the traditional game Siki doka with an increase percentage of 8.65%. T-test analysis shows that tcount is greater than ttable. This indicates that there is a significant difference between the pre-test and post-test, which shows an increase in the physical fitness of class V students at SD Negeri Dendeng, Kupang Regency after being taught both through the foreign traditional game Gala and the traditional game siki doka.